High Density Polyethylene (HDPE) Vessel of Pompong as a Fishing Vessel for Bengkalis Fisherman - Siswandi B; Wasis Dwi Aryawan (IPTEK Journal of Proceedings Series, 2017)
Abstract¾Generally vessels of pompong are made from wood. In this era, wood for shipbuilding is difficult to obtain. So, it is necessary to find an alternative material as a substitute for wood. High density polyethylene (HDPE) can be used as of material for shipbuilding because it has advantages such as heat resistant, corrosion resistant and has a long durability. Size vessels with a length of (L) = 8.8 meters, breadth (B) = 1.56 meters, height (H) = 1.05 meters and draft (T) = 0.6 meters which makes the design shape of the vessel of pompong HDPE plastic. The vessel of the pompong plastic has a stability of GZ value of 0.381 meters on the heel of 60 degrees and has a resistance of 0.74 kilonewtons  at a speed of 5 knots.